Extraordinary Black Americans from colonial to contemporary times - Altman, Susan (Chicago : Childrens Press, 1989)
Presents short biographies of ninety-five black Americans from colonial to contemporary times, highlighting their personal achievements and their resulting contributions to the growth of American society.
Includes bibliographical references (p. 236).
Keywords: African Americans -- Biography -- Juvenile literature; African Americans -- Biography